Methyl Jasmonate and Sodium Nitroprusside Jointly Alleviate Cadmium Toxicity in Wheat (Triticum aestivum L.) Plants by Modifying Nitrogen Metabolism, Cadmium Detoxification, and AsA–GSH Cycle - Kaya, Cengiz; Ugurlar, Ferhat; Ashraf, Muhammad; Noureldeen, Ahmed; Darwish, Hadeer; Ahmad, Parvaiz (Frontiers in Plant Science, 2021)
The principal intent of the investigation was to examine the influence of joint application of methyl jasmonate (MeJA, 10 µM) and a NO-donor sodium nitroprusside (SNP, 100 µM) to wheat plants grown under cadmium (Cd as CdCl2, 100 µM) stress. Cadmium stress suppressed plant growth, chlorophylls (Chl), and PSII maximum efficiency (Fv/Fm), but it elevated leaf and root Cd, and contents of leaf proline, phytochelatins, malondialdehyde (MDA) and hydrogen peroxide (H2O2) as well as the activity of lipoxygenase (LOX). MeJA and SNP applied jointly or singly improved the concentrations of key antioxidant biomolecules, e.g., reduced glutathione (GSH) and ascorbic acid (AsA) and the activities of the key oxidative defense system enzymes such as catalase (CAT), superoxide dismutase (SOD), dehydroascorbate reductase (DHAR), glutathione S-transferase (GST), and glutathione reductase (GR). Exogenously applied MeJA and SNP jointly or singly also improved nitrogen metabolism by activating the activities of glutamine synthetase, glutamate synthase, and nitrate and nitrite reductases. Compared with individual application of MeJA or SNP, the combined application of both showed better effect in terms of improving plant growth and key metabolic processes, and reducing tissue Cd content, suggesting a putative interactive role of both compounds in alleviating Cd-toxicity in wheat plants.